Bose-Einstein condensation of magnons in Cs2CuCl4. - Radu, T; Wilhelm, H; Yushankhai, V; Kovrizhin, D; Coldea, R; Tylczynski, Z; Lühmann, T; Steglich, F (2005)
We report on results of specific heat measurements on single crystals of the frustrated quasi-2D spin-1/2 antiferromagnet Cs2CuCl4 (T(N)=0.595 K) in external magnetic fields B<12 T and for temperatures T>30 mK. Decreasing B from high fields leads to the closure of the field-induced gap in the magnon spectrum at a critical field Bc approximately = 8.51 T and a magnetic phase transition is clearly seen below Bc. In the vicinity of Bc, the phase transition boundary is well described by the power law Tc(B) proportional, variant (Bc-B)(1/phi), with the measured critical exponent phi approximately =1.5. These findings are interpreted as a Bose-Einstein condensation of magnons.